Pengaruh Permainan Konstruktif dan Kecerdasan Visual- Spasial Terhadap Kemampuan Matematika Awal Anak Usia Dini - Warmansyah, Jhoni; Amalina, Amalina (Universitas Islam Negeri Imam Bonjol Padang, 2019)
The purpose of this study was to determine the effect of constructive play and visual-spatial intelligence on early mathematical abilities. The approach used is quantitative through an experimental method with 2x2 treatment by level design. This research was conducted on children in kindergarten group B in the city of Padang. The sampling technique uses Stratified cluster random sampling. The number of samples in this study were 40 children. Data collection in this study used an initial mathematical ability test and a spatial visual intelligence test. The data analysis technique in this study used two-way ANOVA to see the main effects and interactions, then using the Tukey test to see simple effects. The results of this study are as follows: 1) Early mathematical abilities provided with constructive games Lego have a higher influence than constructive games Beams (Fhitung= 5,16 > Ftabe (α=0,05)= 4,04). 2) There is an interaction between constructive play and spatial visual intelligence, in general it has a significant effect on the early math skills of kindergarten children in group B (Fhitung = 13,34 > Ftabel (α=0,05) = 4,04). 3) Early mathematical abilities that have high spatial visual intelligence with given constructive games Lego are higher than the initial mathematical abilities with constructive games (Qhitung = 4,24 > Qtabel (α=0,05) = 3,15). 4) Early mathematical abilities that have low spatial visual intelligence with given constructive games Beams have a higher value than the initial mathematical abilities given by constructive games Lego (Qhitung = -2,30 > Qtabel (α=0,05) = -3,15).